Development of an Extended Product Lifecycle Management through Service Oriented Architecture. - Cassina, J.; Cannata, A.; Taisch, M. (Cranfield University Press, 2009)
The aim of this work is to define new business opportunities through the concept of Extended Product Lifecycle Management (ExtPLM), analysing its potential implementation within a Service Oriented Architecture. ExtPLM merges the concepts of Extended Product, Avatar and PLM. It aims at allowing a closer interaction between enterprises and their customers, who are integrated in all phases of the life cycle, creating new technical functionalities and services, improving both the practical (e.g. improving usage, improving safety, allowing predictive maintenance) and the emotional side (e.g. extreme customization) of the product.
Organised by: Cranfield University
Keywords: PLM; Extended Product; Service Oriented Architecture